RAGAM HIAS TRADISIONAL JAWA PADA SINGEP PEDAN BALLROOM HOTEL SAHID JAYA DI SURAKARTA - Eko Sri Haryanto (Institut Seni Indonesia Surakarta, 2012)
Traditional ornament is a regional cultural resources that need to be preserved so that theJavanese cultural values that have been made by previous generations can be passed downto the next generation. One way is to implement ornaments into existing buildings.This studyaims to determine any traditional ornaments used and how the meaning contained therein,and how it relates to the attractiveness of the tourism industry.This study is a qualitative research approach formalist / structuralist with aestheticand symbolic study, the approach to a study conducted at the decoration found on theinterior singep Pedan Ballroom Sahid Jaya Hotel in Surakarta. This study used a qualitativedescriptive method with aesthetic approach as the basis for analyzing. Comparative methodwas also performed to compare with other similar objects. Collection techniques; techniquesof observation, documentation, interviews, and interpretive analysis.Keywords: decorative, traditional, pedan ball room